Forging a Strategic Axis: The Deepening Partnership between Greece and Saudi Arabia - Lyristis, Minas (HAPSc Policy Briefs Series, 2025)
The relationship between Greece and Saudi Arabia has rapidly evolved into a formalized, multi-dimensional strategic partnership, marking a significant development in the Eastern Mediterranean and Middle East. Driven by converging national interests, including Saudi Arabia’s Vision 2030 and Greece’s ambition to become a key regional hub, this alignment is institutionalized through the High-Level Strategic Cooperation Council. Cooperation spans defence, security, economy, investment, energy, digital connectivity, culture, and tourism, underpinned by numerous bilateral agreements. Key initiatives include defence pacts, the "East to Med data Corridor" project, energy interconnection plans, and substantial growth in bilateral trade and investment. This partnership holds considerable geopolitical significance, linking a key EU/NATO member with a pivotal Middle Eastern power, influencing regional dynamics, and aligning with broader connectivity initiatives like IMEC. While promising, the partnership’s long-term success depends on sustained political commitment and navigating regional complexities.